2018
DOI: 10.1038/s41598-018-29611-3
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: The impact of circulating preeclampsia-associated extracellular vesicles on the migratory activity and phenotype of THP-1 monocytic cells

Abstract: A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Pre-eclampsia (PE) is the most studied pathology in the field, and our combined analysis of the 22 studies that compared EV concentrations to normotensive pregnancies, confirmed that PE is usually associated with higher EV levels. However, less than a quarter of the studies (18%; 4/22) reported more than two-fold increase (Kovács et al, 2018a(Kovács et al, , 2018bPillay et al, 2016Pillay et al, , 2020Verma et al, 2018). Additionally, three studies reported a two-fold decrease in EV levels in PE compared to healthy controls in the third trimester (Lok et al, 2008;Lok, Christine et al, 2009;Pillay et al, 2016).…”
Section:  Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pre-eclampsia (PE) is the most studied pathology in the field, and our combined analysis of the 22 studies that compared EV concentrations to normotensive pregnancies, confirmed that PE is usually associated with higher EV levels. However, less than a quarter of the studies (18%; 4/22) reported more than two-fold increase (Kovács et al, 2018a(Kovács et al, , 2018bPillay et al, 2016Pillay et al, , 2020Verma et al, 2018). Additionally, three studies reported a two-fold decrease in EV levels in PE compared to healthy controls in the third trimester (Lok et al, 2008;Lok, Christine et al, 2009;Pillay et al, 2016).…”
Section:  Discussionmentioning
confidence: 99%
“…For many pathologies, fold-changes both >1 and <1 were reported (results summarised in Table S2). Despite PE being widely reported to be associated with increased circulating EVs, this is not always the case, with three studies (Lok et al, 2008, Lok et al, 2009bPillay et al, 2016) reporting a two-fold decrease in EV levels in PE compared to healthy controls in the third trimester, and less than a quarter of the studies (18%; 4/22) reporting more than a two-fold increase (Kovács et al, 2018a(Kovács et al, , 2018bPillay et al, 2016Pillay et al, , 2020Verma et al, 2018).…”
Section:  Changes In Circulating Ev Concentrations In Pregnancy Pa...mentioning
confidence: 96%
See 3 more Smart Citations